先化简4-a^2/a^2+6a+9 ÷a-2/2a+6 +2再任选一个喜欢的数带入求值
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/04 09:40:06
先化简4-a^2/a^2+6a+9÷a-2/2a+6+2再任选一个喜欢的数带入求值先化简4-a^2/a^2+6a+9÷a-2/2a+6+2再任选一个喜欢的数带入求值先化简4-a^2/a^2+6a+9÷
先化简4-a^2/a^2+6a+9 ÷a-2/2a+6 +2再任选一个喜欢的数带入求值
先化简4-a^2/a^2+6a+9 ÷a-2/2a+6 +2再任选一个喜欢的数带入求值
先化简4-a^2/a^2+6a+9 ÷a-2/2a+6 +2再任选一个喜欢的数带入求值
(4-a^2)/(a^2+6a+9) ÷(a-2)/(2a+6) +2
=(2+-a)(2-a)/(a+3)^2 ×2(a+3)/(a-2) +2
=-2(2+a)/(a+3)+2
a=0,-4/3+2=2/3
a-2a+3a-4a+5a-6a+7a-8a+9a-10a+11a.+99a-100a=
分式的乘除:16-a平方/a平方+8a+16÷a-4/2a+8乘a-2/a+281-a平方/a平方+6a+9÷a-9/2a+6乘a+3/a+9
(4-2a)(a^2-6a+9)÷(3a-a^2)(a^2+2a-15)今天就要
先化简,再求(a^2-4a+4)分之3a+9÷(a+3)×(a+3)分之(a^2+a-6)其中2a-b+2先化简,再求(a^2-4a+4)分之3a+9÷(a+3)×(a+3)分之(a^2+a-6)其中2a-b+2的绝对值+(3a+二分之三)^2=0
先化简(4-a^2/a^2+6a+9)/(a-2/2a+6)+2
化简:a^2+2a/a^2-6a+9÷a^2-4/a^2-3a-a/a-2
a-2/a-3÷a^2-4/a^2+6a+9
a-2a+3a-4a+5a-6a+...+99a-100a
化简; a-2a+3a-4a+5a-6a+``````-2006a+2007a.
(a+3a+5a+...+2009a)-(2a+4a+6a+...+2008a)=
(a+3a+5a+.+2009a)-(2a+4a+6a+.2008a)
计算(a+3a+5a+...+2009a)-(2a+4a+6a+...+2010a)
(a+3a+5a+...+2013a)-(2a+4a+6a+...+2012a)=
化简:a-2a+3a-4a+5a-6a+.+2010a+2011a.
计算(a+3a+5a+.+2003a)-(2a+4a+6a+...+2004a)
(a+3a+5a+.+2003a)-(2a+4a+6a+.+2004a)
(a+3a+5a...+2009a)-(2a+4a+6a+...+2010a)=?
合并同类项:a-2a-3a+4a+5a-6a-7a+8a+9a-10a-11a+12a+……+2008a+2009a-2010a-2011a